Linguistic landscapes in the sociolinguistic and foreign language teaching research field in the Czech Republic - Janikova, Vera (Glottodidactica, 2026)
This article investigates the potential of incorporating the sociolinguistic concept of the Linguistic Landscape (LL) into foreign language teaching, with particular attention to its applicability as a valuable supplementary resource in language education. Following a definition of the LL framework and a summary of current theoretical and methodological discussions, the article presents a concise overview of the development of this expansive sociolinguistic field, with a specific focus on the status of LL research within the Czech context. The analysis then turns to the didactic implications of the LL, exploring its utility in foreign language instruction. Drawing on illustrative examples and the author’s own teaching experience, the article demonstrates practical applications of LL in the teaching of German as a Foreign Language, both in teacher education and classroom practice, within the urban environment of Brno, Czech Republic.